Inflammatory stimuli modulates the expression of ceruloplasmin at surface of human peripheral blood mononuclear cells - Bispo, C. (2011)
Atherosclerosis (ATH) is recognized as a chronic inflammatory condition and it is the leading cause of cardiovascular disease. Atherogenesis is characterized by the passage of LDL through the endothelial layer, and the early infiltration and activation of peripheral blood lymphocytes (PBL) and monocytes (PBMN) that contribute to a pro-inflammatory state in specific locations. However, the functional interaction between immune cells and the oxidation of LDL are still not fully understood. One hypothesis for the etiopathogeny of ATH may be associated with an ongoing inflammatory process caused by an pro-oxidant/antioxidant imbalance induced by metals such as iron (Fe) or copper (Cu). Ceruloplasmin (Cp) is an acute-phase protein but also a multicopper oxidase with a relevant role in Fe metabolism mainly due to its ferroxidase activity. Herein, we aim to study the effect of putative pro-atherogenic immune stimuli on the expression of Cp at the surface of peripheral blood mononuclear cells (PBMC). In order to achieve this goal, PBMC were isolated from human peripheral blood, cultured in different inflammatory and/or altered Fe/Cu status conditions and analysis of Cp expression at cell surface was performed using flow cytometry. Cell surface expression of Cp was shown to be differently modulated by several tested treatments. Importantly, PBMN incubated with IL-1β showed a significant increase of Cp expression compared to untreated cells. Similar results were found using phorbol-12-myristate-13-acetate. Also, higher cell surface expression of Cp was consistently observed in PBMN compared to PBL and in activated vs non-activated cells. These results demonstrate that inflammatory mediators could be, at least in part, involved in the modulation of Cp expression at surface of PBMC and thus, have a putative role in atherogenesis.